Rheological characteristics and stability of fuel slurries based on coal processing waste, biomass and used oil; Fuel; Vol. 302 - Kuznetsov G. V. Geny Vladimirovich; Romanov D. S. Daniil Sergeevich; Vershinina K. Yu. Kseniya Yurievna; Strizhak P. A. Pavel Alexandrovich (2021, 2021)
Title screen